2000
DOI: 10.1002/1521-3757(20001117)112:22<4287::aid-ange4287>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized Pd145(CO)x(PEt3)30 Containing a Capped Three-Shell 145-Atom Metal-Core Geometry of Pseudo Icosahedral Symmetry

Abstract: Presented herein are the geometrical features of a stoichiometric capped three-shell palladium carbonyl phosphane cluster 1. Its pseudo I h metal core (see Figure 1) consists of a central Pd atom surrounded by 12 Pd atoms (shell 1), which in turn are encapsulated by 42 Pd atoms (shell 2), which in turn are encapsulated by 60 Pd atoms (shell 3). Thirty additional Pd atoms cap the 30 square polygons of the third-shell polyhedron with a triethylphosphane ligand attached to each capping Pd atom. It is currently pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 43 publications
(12 reference statements)
4
31
0
1
Order By: Relevance
“…2e), where the numbers 5, 4, and 3 represent faces around that vertex, respectively, 5-gons, 4-gons, and 3-gons. Of note, the outer Ag 60 shell is geometrically reminiscent of the third shell (Pd 60 ) in Dahl's Pd 145 cluster 15 . All vertices on these three polyhedra are Ag(I) atoms, and all edges are built from the connection of adjacent two Ag atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2e), where the numbers 5, 4, and 3 represent faces around that vertex, respectively, 5-gons, 4-gons, and 3-gons. Of note, the outer Ag 60 shell is geometrically reminiscent of the third shell (Pd 60 ) in Dahl's Pd 145 cluster 15 . All vertices on these three polyhedra are Ag(I) atoms, and all edges are built from the connection of adjacent two Ag atoms.…”
Section: Resultsmentioning
confidence: 99%
“…ncouraged by masterpieces of self-assembly in biology [1][2][3][4][5] , some seminal metal clusters 6 of nanometer size have been assembled from simple components [7][8][9][10][11][12] , such as Al 77 13 , Gd 140 14 , Pd 145 15 , Ag 374 16 , and Au 246 17 . Among families of metal clusters, silver nanoclusters benefit from the exceptional versatility of silver(I) atoms, which have flexible coordination preferences, a tendency to form argentophilic interactions and a susceptibility to reduction, all properties enriching the number of members and types of this family [18][19][20] .…”
mentioning
confidence: 99%
“…[1] Beispielsweise finden sich darunter Arbeiten, in denen über eine Funktionalisierung von Metallnanopartikeln oder die Dimerisierung von Goldnanopartikeln mittels verbrückender Moleküle berichtet wird. [2] Obwohl es inzwischen schon viele Beispiele für die Synthese großer Cluster-Moleküle gibt, [3][4][5][6][7][8] wurde der Einfluss von funktionellen Gruppen in der Ligandenhülle solcher Cluster bislang wenig untersucht. Die meisten bisher publizierten Arbeiten beschäftigen sich mit Ligandenaustauschreaktionen.…”
Section: Introductionunclassified
“…In 2008, Chaki et al 19 demonstrated mass spectrometrically that the clusters comprised only 144 Au atoms (plus the 59-60 thiolate ligands), rather than the expected 145 count established previously for Pd 145 by Tran et al 18 This surprise prompted O. López-Acevedo et al 20 to verify by DFT-based optimization that the more stable version centered on a vacancy, i.e. its central I h -Au 12 cage is hollow, lacking a central atom, consistent with the reformulation Au 144 (SR) 60 .…”
Section: Introductionmentioning
confidence: 92%
“…First reports of a singular, 'ubiquitous', Au cluster of approximately ∼145-atoms (core mass ∼29-kDa) date to 1995-6. 17 Next, a primitive structure-model was tested, derived directly from the 'I h -Pd 145 structure' (hereafter denoted simply by 'Pd 145 structure') 18 that had been totally solved by 1999. (See brief description immediately below.)…”
Section: Introductionmentioning
confidence: 99%